AB0407 Undercarboxylated osteocalcin, insulin and lipid profiles do not correlate in patients with rheumatoid arthritis or in healthy volunteers. (23rd January 2014) - Tada, M.; Koike, T.; Okano, T.; Sugioka, Y.; Mamoto, K.; Wakitani, S.; Nakamura, H.
Abstract : Background: Insulin signaling in osteoblasts regulates bone and glucose metabolism 1 . Undercarboxylated osteocalcin (ucOC) promotes insulin sensitivity in osteoblasts and stimulates insulin secretion by pancreatic β cells 2, 3 . Thus, bone and lipid metabolism might be associated with rheumatoid arthritis (RA). Objectives: To determine relationships among ucOC, insulin and lipid metabolism in patients with RA and in healthy volunteers from the prospective cohort TOMORROW (TO tal M anagement O f R isk factors in R heumatoid arthritis patients to lOW er morbidity and mortality; clinical trial registration number, UMIN000003876) study of patients with rheumatoid arthritis (RA) and healthy volunteers. Methods: We compared 204 patients with RA and 202 age- and sex-matched healthy volunteers (female, n=341; RA, n=171; healthy volunteers, n=170; male, n=63; RA, n=31; healthy volunteers, n=32). The TOMORROW study measured body mass index (BMI), bone metabolic markers, dual energy X-ray absorptiometry (DXA), markers of lipid metabolism and inflammation and levels of anti-cyclic citrullinated peptide. We investigated correlations among serum ucOC and bone, glucose, lipid metabolism markers to determine whether any of them are influenced by ucOC using multiple regression analysis. Data were statistically analyzed using Stat view version 5.0 software and values of p<0.05 were considered significant. Results: Mean ucOC values tended to be higher in patients with RA than in volunteers (5.02±4.22 vs. 4.35±2.56 ng/mL; no significant difference). Neither ucOC nor insulin correlated in either group (patients: r = -0.041, p=0.5663; volunteers: r = -0.037, p=0.6008, respectively). The bone metabolic markers, osteocalcin, BAP (bone-specific alkaline phosphatase) and NTx (N-telopeptide cross-links of type 1 collagen) closely correlated with ucOC, whereas the glucose and lipid metabolic markers of total cholesterol, triglyceride, LDL and HDL cholesterol and apoprotein did not. Conclusions: Although a relationship between ucOC and insulin has been determined in animal experiments, these factors did not correlate either in patients with RA or in healthy volunteers. Because various factors are involved in insulin secretion, the degree to which ucOC influences insulin homeostasis in humans should be determined. ucOC, insulin and lipid metabolism were not correlated in patients with RA or in healthy volunteers. References: Clemens TL, Karsenty G. The osteoblast: an insulin target cell controlling glucose homeostasis. J Bone Miner Res. 2011; 26:677-80. Ferron M, Hinoi E, Karsenty G, et al. Osteocalcin differentially regulates beta cell and adipocyte gene expression and affects the development of metabolic diseases in wild-type mice. Proc Natl Acad Sci U S A. 2008; 105:5266-70. Hinoi E, Gao N, Jung DY, et al. The sympathetic tone mediates leptin's inhibition of insulin secretion by modulating osteocalcin bioactivity. J Cell Biol. 2008; 183:1235-42. Disclosure of Interest: M. Tada: None Declared, T. Koike Grant/Research support from: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, T. Okano: None Declared, Y. Sugioka: None Declared, K. Mamoto: None Declared, S. Wakitani: None Declared, H. Nakamura Grant/Research support from: Chugai Pharmaceutical, Astellas Pharma Inc., Janssen Pharmaceutica, GlaxoSmithKline, Pfizer Inc. and Daiichi Sankyo, INC., Speakers Bureau: Ono Pharmaceutical